2001
DOI: 10.1144/petgeo.7.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Underground gas storage: estimating gas column height and saturation with time lapse seismic

Abstract: Seismic monitoring is often used to check hydrocarbon movements during production. On the site of Céré-la-Ronde, an underground water-bearing gas storage facility developed by Gaz de France, a methodology has been implemented for estimating gas column height and saturation with time lapse seismic. The methodology is based on the Gassmann model, on the measurement of time-shifts and on the computation of a specific seismic function. The time-shifts obtained by cross-correlation techniques are used to derive the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In these studies, consideration has been given to both seismic amplitudes (Huang et al . 2001) and reflector time‐shifts (Dumont et al 2001) as possible attributes for monitoring purposes but it is found that the results from amplitude and time‐shift analyses differ substantially. These differences are indicative of the degree of calibration of the seismic product and the complexity of the reservoir geology but are central to understanding the quantitative nature of the 4D seismic signal.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, consideration has been given to both seismic amplitudes (Huang et al . 2001) and reflector time‐shifts (Dumont et al 2001) as possible attributes for monitoring purposes but it is found that the results from amplitude and time‐shift analyses differ substantially. These differences are indicative of the degree of calibration of the seismic product and the complexity of the reservoir geology but are central to understanding the quantitative nature of the 4D seismic signal.…”
Section: Introductionmentioning
confidence: 99%
“…Two lines of walk away VSP have been recorded (Mari et al, 2000;Dumont et al, 2001). Line VSP-M01, orientated north-south, consists of 103 vibrating points with a maximum offset to the source of 800 m. Line VSP-M02, orientated east-west, consists of 60 vibrator points and the maximum offset to the source is 500 m. The vibrators performed sweeps in the 16-120 Hz frequency interval.…”
Section: Permanent Downhole Geophonesmentioning
confidence: 99%
“…estimate the porosities and the gas saturation along the walk away profiles (Mari et al, 2000;Dumont et al, 2001).…”
Section: Permanent Downhole Geophonesmentioning
confidence: 99%
“…(1998) use time‐lapse seismics to monitor a CO 2 flood for reservoir flow anisotropy and permeability structure. With time, more extensive surveys of large‐scale production systems were essayed with repeat surface seismic surveys, highlighting the importance of the time‐lapse images, but also the need for repeatable sources and stable sensors in acquiring useful time‐lapse images (Christie & Ebrom 2000; Dumont et al . 2001).…”
Section: Introductionmentioning
confidence: 99%